Characterization theorem for Laguerre- Hahn orthogonal polynomials on non-uniform lattices - Rebocho, M. N. (2020)
A characterization theorem for Laguerre–Hahn orthogonal polynomials on non-uniform lattices is stated and proved.This theorem proves the equivalence between the Riccati equation for the formal Stieltjes function, linear first-order difference relations for the orthogonal polynomials as well as for the associated polynomials of the first kind, and linear first-order difference relations for the functions of the second kind.